Imaging of strain and lattice orientation by quick scanning X‐ray microscopy combined with three‐dimensional reciprocal space mapping. (1st April 2014) - Chahine, Gilbert André; Richard, Marie‐Ingrid; Homs‐Regojo, Roberto Arturo; Tran‐Caliste, Thu Nhi; Carbone, Dina; Jaques, Vincent Louis Robert; Grifone, Raphael; Boesecke, Peter; Katzer, Jens; Costina, Ioan; Djazouli, Hamid; Schroeder, Thomas; et al.
<x xml:space="preserve">Abstract</x> Numerous imaging methods have been developed over recent years in order to study materials at the nanoscale. Within this context, scanning X‐ray diffraction microscopy has become a routine technique, giving access to structural properties with sub‐micrometre resolution. This article presents an optimized technique and an associated software package which have been implemented at the ID01 beamline (ESRF, Grenoble). A structural scanning probe microscope with intriguing imaging qualities is obtained. The technique consists in a two‐dimensional quick continuous mapping with sub‐micrometre resolution of a sample at a given reciprocal space position. These real space maps are made by continuously moving the sample while recording scattering images with a fast two‐dimensional detector for every point along a rocking curve. Five‐dimensional data sets are then produced, consisting of millions of detector images. The images are processed by the user‐friendly X‐ray strain orientation calculation software (XSOCS), which has been developed at ID01 for automatic analysis. It separates tilt and strain and generates two‐dimensional maps of these parameters. At spatial resolutions of typically 200–800 nm, this quick imaging technique achieves strain sensitivity below Δa/a = 10−5 and a resolution of tilt variations down to 10−3° over a field of view of 100 × 100 µm.